Surface-Related States in Oxidized Silicon Nanocrystals Enhance Carrier Relaxation and Inhibit Auger Recombination - Othonos, Andreas (Springer, 2008)
We have studied ultrafast carrier dynamics in oxidized silicon nanocrystals (NCs) and the role that surface-related states play in the various relaxation mechanisms over a broad range of photon excitation energy corresponding to energy levels below and above the direct bandgap of the formed NCs. Transient photoinduced absorption techniques have been employed to investigate the effects of surface-related states on the relaxation dynamics of photogenerated carriers in 2.8 nm oxidized silicon NCs. Independent of the excitation photon energy, non-degenerate measurements reveal several distinct relaxation regions corresponding to relaxation of photoexcited carriers from the initial excited states, the lowest indirect states and the surface-related states. Furthermore, degenerate and non-degenerate measurements at difference excitation fluences reveal a linear dependence of the maximum of the photoinduced absorption (PA) signal and an identical decay, suggesting that Auger recombination does not play a significant role in these nanostructures even for fluence generating up to 20 carriers/NC.